Evaluating Customer Trust towards Online SNSs sellers using Fuzzy AHP - Ramli R.; Ibrahim A.Z.M.; Bakar A.A.; Mohamad A.H. (Institute of Physics Publishing, 2023)
Hierarchical systems; Sales; Sports; Analytical Hierarchy Process; Business platforms; Customer trust; Fuzzy AHP; Online sellers; Physical interactions; Social commerces; Social Network Sites; Social networking (online)